Blood pressure variability and early neurological outcomes in acute and subacute stroke in Southwestern Ugand - Kulaba, Nicholas; Kayanja, Adrian; Serubiri, Denis; Mukasa, Mark Kaddu; Kaddumukasa, Martin; Nakibuuka, Jane; Moore, Shirley M.; Katabira, Elly T.; Sajatovic, Martha; O’Carroll, Cumara B.; Muyingo, Anthony (eNeurologicalSci, 2023)
Background: Greater blood pressure variability has detrimental effects on clinical outcome after a stroke; its effects are controversial and have not been evaluated in Sub-Saharan Africa (SSA). Methods: We conducted a prospective study of patients with CT head confirmed ischemic and hemorrhagic strokes admitted to a tertiary hospital within 7 days of onset of unilateral neurological deficits. Blood pressure variability indices, standard deviation (SD) and coefficient of variation (CV) of systolic and diastolic blood pressure between day 0 and day 7, were calculated with a subsequent modified Rankin Scale (mRS) score on day 14 post-stroke. Linear regression was performed to determine the exponential coefficients of mortality at 14 days’ post- stroke. Results: Out of 120 patients, 51.7% were female, 52.5% had ischemic stroke and the overall median age was 65 (IQR 54–80) years. Twenty (16.7%) patients died within a median survival time of 7 days, while 32 (26.7%) died by day 14 post-stroke. Patients with hemorrhagic stroke had an overall SDSBP of 16.44 mmHg while those with ischemic stroke had an overall SDSBP of 14.05 mmHg. In patients with ischemic stroke, SDSBP had adjusted coefficients of 1, p = 0.004 with C⋅I: 1.01–1.04 and NIHSS had adjusted coefficients of 1, p = 0.019 with C⋅I: 1.00–1.03 while in patients with hemorrhagic stroke, SDSBP had adjusted coefficients of 1, p = 0.045 with C⋅I: 1.00–1.04 and NIHSS had adjusted coefficients of 1, p ≤0.001 with C⋅I: 1.01–1.03. Conclusion: Exponential increase in Blood Pressure Variability (BPV) and stroke severity scale were independently associated with early mortality among all stroke patients in our study. We recommend future studies to evaluate whether controlling BPV among patients with stroke in Sub-Saharan Africa can reduce mortality.
Keywords: Blood pressure variability; Stroke; Outcomes; Cerebral infarction; Intracerebral hemorrhage; Sub-Saharan Africa